2018
DOI: 10.1007/s12928-018-0511-3
|View full text |Cite
|
Sign up to set email alerts
|

Two-year results after coronary stenting of small vessels in Japanese population using 2.25-mm diameter sirolimus-eluting stent with bioresorbable polymer: primary and long-term outcomes of CENTURY JSV study

Abstract: Percutaneous coronary intervention (PCI) in coronary artery disease (CAD) with very small vessels remains challenging. The aim of this study is to evaluate the safety and effectiveness of the 2.25-mm diameter Ultimaster sirolimus-eluting stent in the treatment of Japanese patients with CAD due to lesions in very small vessels. The CENTURY JSV study is a prospective, multicentre, single-arm study. Seventy patients with lesions deemed suitable for implantation of a 2.25-mm diameter stent were enrolled at seven h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Of note, none of these studies used intracoronary imaging to determine vessel size before study inclusion, which might have contributed to the important observed differences between the vessel size-based inclusion criteria and actual reference vessel diameters (Tables 1 [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] and 2 [10][11][12][34][35][36][37] ).…”
Section: Recommendations For Standardized Definitions Of Small Vessel...mentioning
confidence: 99%
“…Of note, none of these studies used intracoronary imaging to determine vessel size before study inclusion, which might have contributed to the important observed differences between the vessel size-based inclusion criteria and actual reference vessel diameters (Tables 1 [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] and 2 [10][11][12][34][35][36][37] ).…”
Section: Recommendations For Standardized Definitions Of Small Vessel...mentioning
confidence: 99%
“…The design of the CENTURY JSV study has been published earlier [11]. Briefly, it was a prospective, multicenter, single-arm study that enrolled patients with a minimum age of 20 years with asymptomatic myocardial ischemia, stable or unstable angina pectoris with a lesion suitable for implantation of a single 2.25 mm-diameter Ultimaster stent.…”
Section: Study Design and Patient Populationmentioning
confidence: 99%
“…The current CENTURY JSV study was initiated to evaluate the safety and efficacy of the 2.25 mm-diameter Ultimaster stent and the 9-month angiographic and 2-year clinical outcomes have been reported earlier [11]. This update report has the final 5-year outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical in-stent restenosis within 1 year after percutaneous coronary intervention has been remarkably reduced with the advent of drugeluting stents (DESs). [1][2][3] However, very late in-stent restenosis (VL-ISR) is occasionally observed few years after implantation. A previous study reported that VL-ISR develops in 3% of cases after DES implantation; this incidence is approximately five times higher than that of very late stent thrombosis.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical in‐stent restenosis within 1 year after percutaneous coronary intervention has been remarkably reduced with the advent of drug‐eluting stents (DESs) . However, very late in‐stent restenosis (VL‐ISR) is occasionally observed few years after implantation.…”
Section: Introductionmentioning
confidence: 99%